Ultrasonic tomography for multiphase flow application - Abdul Rahim, Ruzairi; Amari, Hudabiyah Arshad; Mohd. Hafiz Fazalul, Rahiman (Pusat Pengurusan Penyelidikan (RMC) & Penerbit UTM Press, 2010)
Characterizing multiphase flow dynamics and estimating phase composition are important in many applications including oil/gas production. Conceptually ultrasonic travel-time tomography is an appealing method. It estimates flow phase composition by mapping out the sound speed distribution over a cross section or volume traversed by a large number of travel paths. However, low sound speed contrast over multiphase mixtures imposes high accuracy requirement in travel time estimation which can be especially challenging in the presence of dispersion and multipath interference. On the other hand, high impedance contrast between phases, such as at gas/liquid interfaces, introduces significant losses and hence leads to reduced signal versus noise ratio. In this talk we first provide a characterization of the signal structure based on both numerical wave propagation modeling and lab test data, then we analyze the sensitivity and accuracy requirement for travel time estimation using several different approaches, and finally we evaluate the performance of flow imaging and phase estimation for several common compositional scenarios.